Analysis of The Effect of Gross Regional Domestic Product, Number of Population, Regional Minimum Wage, Open Unemployment Rate, and Human Development Index on Poverty in 2010-2020 East Java Province - Fajriah, Nur Ahmar (Jurnal Ilmu Ekonomi Terapan, 2021)
Poverty is an economic problem experienced by almost all regions in Indonesia, including East Java Province, where poverty in East Java is relatively high in 2016 East Java Absolute poverty of 4.78 million people. Therefore, it is necessary to find a solution to overcome the problem or reduce poverty. This study aims to analyze the effect of Gross Regional Domestic Product (GRDP), population, Regional Minimum Wage (UMR), open unemployment rate and Human Development Index (IPM) on poverty in East Java Province in 2010-2020. This research uses panel data method with fixed effect model approach, and the data used is secondary data. Adjusted R2 value is quite high. then the results of this study are the variables of GRDP, population, open unemployment rate and HDI have a significant effect on poverty, while the UMR variable has no significant effect on poverty. Therefore, the development of GRDP, population, open unemployment rate should be considered to overcome the problem of poverty. Keywords: Gross Regional Domestic Product, population, Regional Minimum Wage, Open Unemployment Rate, Human Development Index JEL: P24, J11, J31, J64, O15